Industrial high-voltage-resistant X-ray tube insulation structure and preparation method thereof

By providing a titanium-based composite coating on the glass surface of the X-ray tube, the problems of insulation breakdown and thermal stress damage of the glass insulation shell under high voltage are solved, the service life of the X-ray tube is extended and the surface performance is improved, making it suitable for a variety of complex environments.

CN120600608APending Publication Date: 2025-09-05HANGZHOU KAILONG MEDICAL INSTR
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510783420.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-12
Publication Date
2025-09-05

AI Technical Summary

Technical Problem

The glass insulating shell of existing industrial high-kilovolt X-ray tubes is easily susceptible to electron avalanche effect caused by the accumulation of secondary electrons under high voltage, leading to insulation breakdown, thermal stress damage and surface performance degradation, with a service life of less than 5,000 hours.

Method used

A titanium-based composite coating, including a bottom titanium film and a titanium oxide transition layer, is set on the surface of the X-ray tube glass through magnetron sputtering technology to enhance the insulation performance and reduce the accumulation of secondary electrons, preventing electron avalanche and thermal stress damage.

Benefits of technology

It significantly improves the insulation breakdown field strength of the X-ray tube, reduces the secondary electron yield, extends the service life to more than 8,000 hours, and improves the surface hardness and wear resistance, making it suitable for humid, high-radiation and chemically corrosive environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to an industrial high-voltage-resistant X-ray tube insulation structure and a preparation method thereof.The industrial high-voltage-resistant X-ray tube insulation structure is X-ray tube glass with the surface provided with a titanium-based composite coating, the titanium-based composite coating comprises a bottom titanium film and a titanium oxide transition layer, and the thickness of the bottom titanium film ranges from 50 nm to 80 nm; the thickness of the titanium oxide transition layer is 10-20 nm, the dielectric constant of the titanium oxide transition layer is larger than or equal to 80, and the leakage current density is smaller than 1 * 10 A / cm. The preparation method comprises the following steps: S1, pretreating X-ray tube glass, wherein the surface roughness Ra after pretreatment is less than 1 nm; s2, magnetron sputtering titanium plating is carried out, and a titanium-based plating layer is formed; and S3, in-situ oxidation is carried out, trace oxygen is introduced into the vacuum chamber, vacuum annealing is carried out, a titanium oxide transition layer is formed on the upper portion of the titanium-based coating, and a bottom titanium film is formed on the lower portion of the titanium-based coating. Insulation resistance and thermal stress damage resistance are achieved at the same time, and surface performance degradation is prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to an industrial high-voltage X-ray tube insulation structure and a preparation method thereof, and in particular to a high-insulation high-voltage X-ray tube structure manufactured by magnetron sputtering titanium film coating technology on the surface of an insulating medium and a preparation method thereof. Background Art

[0002] Currently, industrial high-kilovolt X-ray tubes generally use glass as the insulating shell, which faces the following technical bottlenecks: 1. Insulation failure risk: Under continuous high voltage (>150 kV) conditions, the glass surface is prone to electron avalanche effect caused by the accumulation of secondary electrons, resulting in insulation breakdown; 2. Thermal stress damage: When the temperature of the anode area exceeds 300°C, cracks will appear at the seal between the glass and the metal due to the difference in thermal expansion coefficient; 3. Surface performance degradation: High-energy electron bombardment causes ablation of the glass surface, accelerating the degradation of insulation performance, and the average lifespan is less than 5,000 hours.

[0003] The existing patent publication number is CN221668767U, and the utility model patent name is "An Industrial Glass X-ray Tube". It proposes an integrated insulating shell structure, which improves the X-ray tube's anti-puncture capability, but does not solve the problem of surface secondary electron emission. It cannot simultaneously achieve anti-insulation, resistance to thermal stress damage, and prevention of surface performance degradation. Summary of the Invention

[0004] The technical problem solved by the present application is to overcome the above-mentioned deficiencies in the prior art and provide an industrial high-voltage X-ray tube insulation structure and a preparation method thereof that can simultaneously achieve resistance to insulation, resistance to thermal stress damage, and prevention of surface performance degradation.

[0005] The basic principle of this application is to improve the insulation performance of the X-ray tube by providing a titanium-based thin film coating on the X-ray tube glass. On the one hand, the titanium coating makes the surface smoother and prevents the generation of secondary electrons. On the other hand, the titanium coating increases a certain degree of conductivity to prevent the accumulation of secondary electrons, thereby reducing the possibility and degree of thermal stress damage and surface performance degradation of the X-ray tube and extending the service life of the X-ray tube.

[0006] The technical solution adopted by the present application to solve the above-mentioned technical problems includes: an industrial high-voltage resistant X-ray tube insulation structure, characterized in that: the industrial high-voltage resistant X-ray tube insulation structure is an X-ray tube glass (substrate, insulating medium) with a titanium-based composite coating provided on the surface, the titanium-based composite coating comprising a bottom titanium film and a titanium oxide transition layer, the bottom titanium film having a thickness of 50-80 nm; the titanium oxide transition layer having a thickness of 10-20 nm, a dielectric constant of ≥80, and a leakage current density of <1×10⁻ 9A / cm². This application utilizes a titanium-based composite coating on an insulating medium to achieve a certain degree of smoothness and conductivity while maintaining insulation strength. This prevents the generation and accumulation of secondary electrons, significantly reducing the likelihood and extent of electron avalanche effects caused by secondary electron accumulation. This increases the high-voltage stability of high-kV industrial tubes during long-term continuous use, effectively reducing the likelihood and extent of thermal stress damage and surface performance degradation in X-ray tubes, and extending the service life of X-ray tubes.

[0007] Preferably, the thickness of the titanium oxide transition layer is between 12 nm and 18 nm, and the thickness of the underlying titanium film is between 55 nm and 75 nm.

[0008] The bottom titanium film of the present application can be formed on the lower part of the titanium-based coating by magnetron sputtering deposition, with a sputtering power of 300-600 W and an argon pressure (bias) of 0.5-1.0 Pa.

[0009] The titanium oxide transition layer described in the present application is formed by natural oxidation of the upper portion of the titanium-based coating during vacuum annealing.

[0010] The technical solution adopted by the present application to solve the above technical problems also includes: a method for preparing the above industrial high-voltage X-ray tube insulation structure, which is characterized by comprising the following steps: S1 X-ray tube glass pretreatment: plasma cleaning of the X-ray tube glass surface (Ar / O2 mixed gas, power 200 W, time 10 min). After pretreatment, the surface roughness Ra is less than 1 nm. S2 magnetron sputtering titanium coating, using a rotating target in a vacuum chamber to magnetron sputter titanium coating on the X-ray tube glass surface, substrate temperature ≤ 150 ° C, deposition rate 5-10 nm / min, to form a titanium-based coating; S3 is in-situ oxidation, a trace amount of oxygen is introduced into a vacuum chamber, and vacuum annealing is performed, so that a titanium oxide transition layer is formed on the upper part of the titanium-based coating, and a bottom titanium film is formed on the lower part of the titanium-based coating.

[0011] The vacuum annealing is to maintain the temperature at 400°C for 1 hour in a vacuum environment, then reduce the temperature to about 200°C at a rate of 0.5-5°C / min, and then naturally cool to room temperature.

[0012] Preferably, the magnetic field intensity on the target surface during magnetron sputtering is 300-400 Gs.

[0013] Preferably, the bias voltage ratio of argon gas during magnetron sputtering is 0.5-1.0 Pa.

[0014] Preferably, the deposition rate during magnetron sputtering is 6-8 nm / min.

[0015] Preferably, the oxygen pressure ratio during in-situ oxidation is 0.03Pa-0.07Pa.

[0016] This application significantly improves the insulation performance of X-ray tube glass, with the breakdown field strength increased from 15 kV / mm of traditional glass to approximately 23-30 kV / mm; the secondary electron yield is reduced by approximately 25-36%; the reliability is greatly enhanced, with no cracks appearing after 1,000 thermal cycles at 300°C, and the service life extended to more than 8,000 hours; the surface hardness is increased from 5.5 GPa of ordinary glass to 8.2 GPa (nanoindentation test); the TiO2 layer (titanium oxide transition layer) of this application has photocatalytic properties and self-cleaning capabilities; and the application range is expanded, making it suitable for stable operation in humid, high-radiation or chemically corrosive environments (such as nuclear industry inspection and deep-sea equipment flaw detection). DETAILED DESCRIPTION

[0017] The present application will be further described in detail below through examples. The following examples are intended to explain the present application but the present application is not limited to the following examples.

[0018] The main process of the method for preparing the insulation structure of an industrial high-voltage X-ray tube in this application is as follows: S1 substrate (referring to X-ray tube glass) pretreatment: the surface of the X-ray tube glass is plasma cleaned (Ar / O2 mixed gas, power 200 W, time 10 min). After pretreatment, the surface roughness Ra is less than 1 nm. S2 magnetron sputtering titanium coating: In a vacuum chamber, a rotating target is used to magnetron sputter titanium (99.99% purity) on the surface of the X-ray tube glass. The substrate temperature is ≤150°C and the deposition rate is 5-10 nm / min to form a titanium-based coating. S3 is in-situ oxidized by introducing a trace amount of oxygen (partial pressure 0.01-0.1 Pa) into a vacuum chamber and vacuum annealing, whereby a dense TiO2 layer, i.e., a titanium oxide transition layer, is formed on the upper portion of the titanium-based coating, and a bottom titanium film is formed on the lower portion of the titanium-based coating.

[0019] The vacuum annealing is to maintain the temperature at 400°C for 1 hour in a vacuum environment, then reduce the temperature to about 200°C at a rate of 0.5-5°C / min, and then naturally cool to room temperature.

[0020] The main points of the preparation method include: The vacuum needs to reach 2.66×10⁻ 5 Pa, the working gas pressure is usually 0.133~1.33 Pa. Too high will lead to loose membrane layer, while too low will reduce the ionization rate.

[0021] Sputtering power and voltage: DC sputtering voltage range is -500~-800 V, current 100~600 mA; RF sputtering requires a power supply of 300 W~2 kW, and the power density affects the density of the film layer.

[0022] Gas flow and ratio: Argon is the main working gas, and the flow ratio of the reaction gas (such as O2, N2) (such as O2 / Ar=1.0~1.9) determines the composition of the compound film and needs to be precisely controlled.

[0023] Substrate temperature and bias voltage: Substrate temperature affects the crystallinity of the film (for example, the anatase phase of TiO2 accounts for 50%~98% at 500°C); bias voltage can enhance ion bombardment and improve adhesion.

[0024] Magnetic field strength and target material design: The magnetic field strength on the target surface is 200~500 Gs. Optimizing the magnetic field distribution can improve etching uniformity; the rotating target design can increase utilization.

[0025] Deposition rate and film thickness monitoring: A quartz microbalance is used to monitor the film thickness in real time. The deposition rate is 5-10 nm / min, and the film thickness error must be controlled within ±3%.

[0026] Closed-loop feedback control: Real-time adjustment of process parameters (e.g., gas flow, power) via plasma emission spectra or sensors to ensure stability and repeatability.

[0027] Note: The thickness of titanium-based coating needs to be strictly controlled: When the thickness of the titanium-based coating is too low (Example 1), the high dielectric constant leads to low conductivity, and secondary electrons are still easy to accumulate, and the effect of reducing secondary electrons is average; when the thickness of the titanium-based coating is too high (Example 3), although there is a significant improvement in the reduction of secondary electrons, the dielectric constant decreases significantly, and the breakdown field strength performance is average; when the thickness of the titanium-based coating is at the median value (Example 2), the dielectric constant performance is basically consistent with that of Example 1, and the breakdown field strength is maintained at a high level. At the same time, due to a certain degree of conductivity, the level of reduction of secondary electrons basically reaches the level of Example 3. When the thickness of the titanium-based coating is in the median range, the optimal performance range is reached.

[0028] The main technical advantages of this application: 1. The titanium oxide transition layer can be used to enhance the surface performance and air tightness of glass and exhibits good stability in radiation environments; 2. High hardness and wear resistance. The titanium oxide transition layer is formed into an ultra-hard film through vacuum ion plating technology, which can significantly improve the hardness and wear resistance of the glass surface. The titanium-plated glass surface hardness is improved and the wear resistance is enhanced, thereby reducing the surface damage of the X-ray tube during high-frequency use; 3. Corrosion resistance, thermal stability and high temperature resistance. The titanium oxide transition layer is a naturally generated dense titanium oxide (TiO2) layer with strong corrosion resistance. It can still maintain structural stability at high temperatures and can withstand the high temperature, high vacuum environment and possible chemical erosion inside the X-ray tube; 4. Improve photoelectric performance. Nano-titanium dioxide has wide-bandgap semiconductor properties, which can enhance photoelectric response efficiency. In X-ray tubes, the titanium oxide transition layer can improve the sensitivity and energy conversion efficiency of the device by optimizing the electron emission or signal conduction path; 5. Antibacterial and self-cleaning: the photocatalytic activity of the titanium oxide transition layer (such as nano-TiO2) can decompose surface organic matter and inhibit microbial growth, reducing internal contamination of the X-ray tube, making it particularly suitable for medical or high-cleanliness industrial scenarios; 6. Radiation protection and stability: Titanium-based materials exhibit good stability in radiation environments. Studies have shown that titanium's passivation properties make it stable in oxidizing and weakly reducing media, making it particularly suitable for X-ray tube components exposed to complex working conditions for a long time. For example, lead-free perovskite materials have demonstrated high sensitivity and radiation fatigue resistance in X-ray detection, indirectly supporting the long-term reliability of titanium oxide transition layers in X-ray tubes. 7. Process maturity and economical efficiency: Magnetron sputtering has been widely used in titanium film preparation. For example, continuous titanium film coating technology on steel surfaces achieves large-scale uniform coating by optimizing parameters such as sputtering power and vacuum degree, and can be transferred to glass substrates for application. 8. Cost-effectiveness: The titanium film coating process can reduce costs through large-scale production and adapt to the batch manufacturing needs of X-ray tubes.

[0029] This application significantly optimizes equipment performance and lifespan by improving surface hardness, corrosion resistance, thermal stability, and functionalities such as self-cleaning. The maturity of existing processes (such as magnetron sputtering) and the unique properties of titanium materials (such as the self-healing properties of titanium oxide layers) provide technical support. By coating the glass surface with a titanium film, the surface performance and insulation properties of the glass can be significantly improved, significantly improving the problem of breakdown failure caused by insufficient insulation during high-voltage operation, and extending the service life of the X-ray tube and its high-voltage stability.

Claims

1. An industrial high-voltage X-ray tube insulation structure, characterized by: The industrial high-voltage X-ray tube insulation structure is an X-ray tube glass with a titanium-based composite coating on its surface. The titanium-based composite coating includes a bottom titanium film and a titanium oxide transition layer. The bottom titanium film has a thickness of 50-80 nm. The titanium oxide transition layer has a thickness of 10-20 nm, a dielectric constant of ≥80, and a leakage current density of <1×10⁻. 9 A / cm².

2. The industrial high-voltage X-ray tube insulation structure according to claim 1, characterized in that: The thickness of the titanium oxide transition layer is between 12nm and 18nm, and the thickness of the bottom titanium film is between 55nm and 75nm.

3. The method for preparing an industrial high-voltage X-ray tube insulation structure according to claim 1 or 2, characterized in that The following steps are involved: S1 X-ray tube glass pretreatment, plasma cleaning of the X-ray tube glass surface; S2 magnetron sputtering titanium coating, using a rotating target in a vacuum chamber to magnetron sputter titanium coating on the X-ray tube glass surface, substrate temperature ≤ 150 ° C, deposition rate 5-10 nm / min, to form a titanium-based coating; S3 is in-situ oxidation, a trace amount of oxygen is introduced into a vacuum chamber, and vacuum annealing is performed to form a titanium oxide transition layer on the upper part of the titanium-based coating and a bottom titanium film is formed on the lower part of the titanium-based coating.

4. The method for preparing an industrial high-voltage X-ray tube insulation structure according to claim 3, wherein: The vacuum annealing is to maintain the temperature at 400°C for 1 hour in a vacuum environment, then reduce the temperature to about 200°C at a rate of 0.5-5°C / min, and then naturally cool to room temperature.

5. The method for preparing an industrial high-voltage X-ray tube insulation structure according to claim 3, wherein: The magnetic field intensity on the target surface during magnetron sputtering is 300~400 Gs.

6. The method for preparing an industrial high-voltage X-ray tube insulation structure according to claim 3, wherein: The argon bias ratio during magnetron sputtering is 0.5-1.0 Pa.

7. The method for preparing an industrial high-voltage X-ray tube insulation structure according to claim 3, wherein: The surface roughness Ra after pretreatment is less than 1 nm.

8. The method for preparing an industrial high-voltage X-ray tube insulation structure according to claim 3, wherein: The argon bias voltage ratio during magnetron sputtering was 0.5-1.0 Pa.

9. The method for preparing an industrial high-voltage X-ray tube insulation structure according to claim 3, wherein: The deposition rate during magnetron sputtering is 6-8 nm / min.

10. The method for preparing an industrial high-voltage X-ray tube insulation structure according to claim 3, wherein: The oxygen pressure ratio during in-situ oxidation is 0.03Pa-0.07Pa.

Citation Information

Patent Citations

  • Industrial glass X-ray tube

    CN221668767U